The relationship between red hair, MC1R gene mutation, pain and anesthesia: An integrative literature review (Research, Society and Development, 2021)
Objective: To address the issue of sensitivity in redheads due to alteration in the MC1R gene. Methodology: This is an integrative literature review, carried out in January 2021, in the Virtual Health Library (VHL), PubMed and Google Scholar databases, using articles written in Portuguese or English, published in the period between 2017 and 2021. Results: Of the 135 articles found in total, after methodological rigor through the inclusion and exclusion criteria, 10 articles were selected, 1 article in PUBMED, 8 in Google Scholar and 1 in the VHL. The analysis of the articles found was descriptive and predisposed to the data extraction stage: database, authors/year of publication, origin/language of publication, title and theme. Conclusion: In view of the results found in the literature, one can observe the deficiency of Brazilian studies on the subject, even though it is relevant to the scope of science, considering that it is necessary to know the mechanism behind this mutation and, through the discoveries, strategies that can be developed provide this population with an improvement in their quality of life.